Tourism sectors contribution on the poverty reduction within tourism scope in Central Java - Bambang Guritno (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Through tourism, several problems such as poverty alleviation and unemployment reduction can be solved. The development and development of tourism can bring huge benefits to the Indonesian people, especially the people in the tourist destination areas. The development of tourism plays a role in economic movements that can improve the well-being of communities, such as more open employment, business opportunities for communities, and increased revenue for the communities themselves and the country, especially local governments. This study aims to determine the types of poverty, causes of poverty, and the impact of tourism on the poor population in Central Java's tourist areas. A total of 60 coastal residents were sampled for the study using a purposeful sampling method. Data analysis uses qualitative descriptions. The results of the study are as follows (i) Types of poverty in coastal communities, among which: 60 years old and above, low education level (primary school graduates), and average income below the monthly minimum wage, (ii) The factors that lead to poverty include natural factors, cultural factors and in The lack of poor people working in the tourism sector, and (iii) the impact of tourism on coastal communities is conducive to the creation of new employment opportunities, such as guest diving guests, porters and souvenir sellers by understanding the opportunities and promises to foster entrepreneurship, thereby reducing poverty in the vicinity of tourist villages.